Problems faced by ASHA workers for malarial services under NVBDCP: a cross sectional study - Gohel, Aniruddha; Makwana, Naresh; Rathod, Mittal; Sarkar, Amrita; Parmar, Dipesh (International Journal of Research in Medical Sciences, 2017)
Background: About 95% of the country’s population resides in malaria endemic areas. The NVBDCP is multi-faceted public health programme in the country. The NVBDCP became an integral part of the NRHM launched in 2005. In NRHM, ASHA worker should be placed at grass root level. So role of ASHA is critical at grass root level. Problems faced by ASHA, it will affect the performance. So, ASHA workers positioned at village, Population catered by them, education, work experience, problems related to incentive and any other problems should be considered. The primary objective was to know the problems faced by ASHA workers for malarial services under NVBDCP in Jamnagar district. Methods: A cross-sectional study was conducted in rural areas of the district by using multistage sampling. Results: There was vacant post of ASHA in one village of low performing sub-centre. ASHA having work experience of less than one year was concentrated in poor performing sub-centre villages. More than one third ASHA served > 2000 population and more than half of them belonged to low performing sub centres. Around one sixth ASHA workers had difficulty in getting incentive or any problems. Majority of them belonged to low performing sub centres-villages. Conclusions: Main identified problems were some areas were far to reach by them, getting incentive for work and populations catered by them were too high. Most of them belonged to low performing sub centre-villages. All of above findings had affected the performance of ASHA workers.